Advanced Cut-Edge Characterization Methods for Improved Sheared-Edge Damage Evaluation in High-Strength Sheet Steels - Patrick Larour; Olle Sandin; Daniel Casellas (Metals)
This study investigates shear cutting of high-strength steel sheets, a process known to negatively impact the forming and fatigue properties of the material. The localized deformation near the cut edges imposes sheared-edge damage, especially in advanced high-strength steels where severe shear deformation occurs in the very vicinity of the cut edge. In this work, an extensive experimental investigation was carried out on punched holes of thin sheets, using light optical microscopy and metallographic techniques for sheared-edge damage assessment. These methods provided detailed insights into the sheared-edge damage and offer a thorough understanding of the deformation behavior in the shear-affected zone. Advanced engineering cut-edge investigation methods have been developed based on 2D and 3D stereo light microscopy for non-destructive panoramic cut-edge parameters and cut-edge profile determination along cut-hole circumference. Such methods provide an efficient evaluation instrument for challenging close-cut holes, with the possibility of industrial in-line monitoring and machine learning applications for Industry 4.0 implementation. Additionally, the study compares grain shear angle measurement and Vickers indentation for deformation assessment of the cut edge. It concludes that grain shear angle offers higher resolution. This parameter is therefore postulated as relevant for assessing the sheared-edge zone. The findings contribute to a deeper understanding of sheared-edge damage and improve evaluation methods, potentially enhancing the use of high-strength steels in automotive and safety-critical applications.